Pengembangan Materi BIPA Berbasis Multimedia Dan Berkonten Budaya Lokal - nina setyaningsih; raden arief nugroho; valentina widya suryaningtyas (Jurnal CULTURE (Culture, Language, and Literature Review), 2016)
Currently, many universities and institutions provide Indonesian Language for Foreign Speakers service (BIPA/Bahasa Indonesia bagi Penutur Asing). However, some BIPA materials are considered out of date. This research is aimed at developing a BIPA material to provide an alternative for the existing BIPA materials. The material was developed based on an evaluation conducted on two existing BIPA materials. The BIPA material developed in this research contains multimedia and local content as to accommodate the existing materials that lack both components. Multimedia is needed since in this era of information, the need to catch up with current technology is highly required, while the local contents will facilitate BIPA learners to understand Indonesian expressions and way of thinking. The research suggests that technology and local cultures are essential in developing a BIPA material.   Keywords:  BIPA, material evaluation, material development